Knowledge, Perceptions, and Preferred Information Sources Related to COVID-19 Among Healthcare Workers: Results of a Cross Sectional Survey. Issue 5 (June 2021) - Sathianathan, Shyama; Van Scoy, Lauren Jodi; Sakya, Surav Man; Miller, Erin; Snyder, Bethany; Wasserman, Emily; Chinchilli, Vernon M.; Garman, John; Lennon, Robert P.
Purpose: To compare COVID-19 related knowledge, perceptions, and preferred information sources between healthcare workers and non-healthcare workers. Design: Cross-sectional survey. Setting: Web-based. Subjects: Convenience sample of Pennsylvanian adults. Measures: Primary outcomes were binary responses to 15 COVID-19 knowledge questions weighted by a Likert scale assessing response confidence. Analysis: Generalized linear mixed-effects models to assess comparisons between clinical decision makers (CDM), non-clinical decision makers working in healthcare (non-CDM) and non-healthcare workers (non-HCW). Results: CDMs (n = 91) had higher overall knowledge than non-CDMs (n = 854; OR 1.81 [1.51, 2.17], p < .05). Overall knowledge scores were not significantly different between non-CDMs (n = 854) and non-HCW (n = 4, 966; OR 1.03 [0.97, 1.09], p > .05). Conclusion: The findings suggest a need for improved education about COVID-19 for healthcare workers who are not clinical decision makers, as they play key roles in patient perceptions and compliance with preventive medicine during primary care visits.